Assessment of Alkaline Phosphatase Activity in Hydatid Cyst Protoscolices and Liver Tissue as a Pathological Biomarker - Mojgan Farrokhi Karibozorg; Ali Farahnak; Mohammad Bagher Molaei Rad; Taghi Golmohammadi; Mohammad Reza Eshraghian (Pasteur Institute of Iran, 2014)
Introduction: Hydatid cyst disease is caused by the protoscolices of Echinococcus granulosus. Alkaline phosphatase (ALP) enzyme is required for metabolism, physiology, immunology, and nutrients absorption in parasite. The aim of this study was to compare the level of ALP activity (as a pathological biomarker) in hydatid cyst protoscolices (HCP) with that of sheep liver tissue and to determine the effect of cystic infection on the enzyme activity. Methods: HCPs were collected from sheep livers with hydatid cysts at a local abattoir and washed 3 times with PBS buffer. HCP samples were freeze-thawed and sonicated, while the collected liver tissues were homogenized. Then, extract solutions were centrifuged and stored at -20°C. ALP activity was measured in the extract solutions of HCP and healthy and infected sheep liver tissue samples. The amounts and bands of protein samples were detected using Bradford method and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), respectively. To determine the significant difference between the two groups, independent two samples t-test was used. Results: The mean values of ALP-specific activity of healthy and infected livers and HCP were estimated 0.019, 0.175, and 1.28 U/ml/mg, respectively. Higher ALP activity level was observed in cystic liver compared to healthy liver (p<0.05). T-test analysis showed higher ALP enzyme activity for HCP compared to healthy liver (p<0.05). SDS-PAGE demonstrated a protein band with molecular weight of 59 kDa in HCP samples, which was identified as ALP. Conclusion: ALP activity in HCP and healthy liver indicates the importance of this enzyme in comparative biochemistry of liver and parasite. Higher level of ALP enzyme activity in cystic liver in comparison with healthy liver could be considered as a pathological biomarker for diagnosis of hydatid cyst disease with other hydatid disease parameters.